Elements of Stakeholders in the Design of MSME Simple Financial Records - Elana Era Yusdita; Intan Amalia Fadilah; Sherlyana Juwita Ningrum (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The purpose of this study is to identify stakeholder interests in the preparation of simple financial records. This research is a case study in the batik group of Sidomulyo Village, Madiun Regency. In-depth interviews, document observations, and FGD were taken to obtain valid data for making simple financial records. Interviews were conducted with manager and treasurer, while FGD was conducted with all members of the batik group as interested parties. The result is that managers need to know the cost of goods manufactured, treasurers need cash inflow records, and members need profit-sharing information. There is a need for separation between personal and group resources. The solution is to create a custom recording method and flow. The first product is a Productive Mom's Book (Buku Ibu Produktif) to record the elements that makeup prices, the origin of resources, and proof of profit sharing. The second product is Cash Books to record incoming and outgoing cash belonging to the group. This product has been tried together and received a good response from all elements of the batik group. Students can make SMEs a real accounting information system laboratory.